The Blood is Ḥarām : A critical Review of Halal Industry’s Standard, Based on the Qur’ānic Criterion - Al Husaini, Syed Arif Ali Shah; Muhammad Ishaq (Journal of Islamic and Religious Studies, 2019)
Healthy nourishment depends on healthy food. General consideration of people is of being the food safe and edible for human consumption not its effect on their spiritual selves but the Islamic terms Ḥalāl and Ḥarām emphasis on both physical and internal safety. Islam commands to avoid doubtful and dubious things rather than to use Ḥarām. The unprecedented evolution and advancement of science and technology caused a revolution in the food-science and technology as well. Many new and innovative flavors etc. took place of organic and natural consumables. Accordingly, the Muslims were in dire need of a robust system which would be able to convince them of the Ḥalāl status of the daily consumables. The article investigates the Sharī’ah stand on the issue of blood in the light of Qur’ān, Sunnah and comparative jurisprudence study, and modern sciences related to blood. Keeping in mind the Globalized Halal Industry all the researched is coupled with combined comparative study of all Schools of Islamic Fiqh, to make easy the way of Unified Halaal Standard regarding the blood. Under the main title The paper comprises subtopics of an introduction and few chapters, which deal with definition and functions of blood, types of blood, difference between blood of aquatic and land animals, comparative study of modern sciences related to blood and Shariah status of use of the blood in various industries in term of Halal and Haram.